2012
DOI: 10.1111/j.1468-3148.2011.00670.x
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Psychiatric Disorders in a Total Population of Adults with Intellectual Disability and Challenging Behaviour Using the PAS‐ADD Checklist

Abstract: The data would appear supportive of previous suggestions that it is unlikely that the majority of challenging behaviours in adults with intellectual disability are underpinned by psychiatric disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 24 publications
0
13
0
1
Order By: Relevance
“…Although not all previous research points in that direction [33], it has been suggested that such behavior may be associated with psychiatric disorders in people with ID [34, 35]. If so, seeking psychiatric care based on challenging behavior may be appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…Although not all previous research points in that direction [33], it has been suggested that such behavior may be associated with psychiatric disorders in people with ID [34, 35]. If so, seeking psychiatric care based on challenging behavior may be appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…The sample sizes ranged from n = 24 (Ross & Oliver, 2002) to n = 4,069 (Tsiouris et al., 2011). Sixteen studies were determined to be of high quality (Bernstein et al., 2015; Cervantes & Matson, 2015; Clark et al., 2016; Crocker et al., 2014; Davies et al., 2015; Esbensen & Benson, 2006; Hartley & MacLean, 2007; Hemmings et al., 2006; Horovitz et al., 2013; Koritsas & Iacono, 2015; Matson et al., 2009; Matson & Rivet, 2008; Novaco & Taylor, 2004; Sappok et al., 2014; Tenneij et al., 2009; Tsiouris et al., 2011), the remaining 22 studies were rated as low quality (Alexander et al., 2010, 2015; Allen et al., 2012; Bowring et al., 2017; Crocker et al., 2006; Didden et al., 2009; Drieschner et al., 2013; Hurley, 2008; Larson et al., 2011; Lindsay et al., 2013; Lundqvist, 2013; Lunsky et al., 2012; Nøttestad & Linaker, 2002; Owen et al., 2004; Phillips & Rose, 2010; Rojahn et al., 2004, 2010; Ross & Oliver, 2002; Thorson et al., 2008; Totsika et al., 2008; Turygin et al., 2013; Tyrer et al., 2006). A total of 27 different instruments were used to assess aggressive behaviour.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐five studies reported associations of nine different factors with self‐injurious behaviour (Table 6) (Allen et al., 2012; Bernstein et al., 2015; Bowring et al., 2017; Clark et al., 2016; Crocker et al., 2006; Drieschner et al., 2013; Hemmings et al., 2006; Horovitz et al., 2013; Hurley, 2008; Larson et al., 2011; Lundqvist, 2013; Lunsky et al., 2012; Matson et al., 2009; Matson & Rivet, 2008; Nøttestad & Linaker, 2002; Owen et al., 2004; Rojahn et al., 2004, 2010; Ross & Oliver, 2002; Sappok et al., 2014; Tenneij et al., 2009; Thorson et al., 2008; Totsika et al., 2008; Tsiouris et al., 2011; Turygin et al., 2013). The presence of self‐injurious behaviour was based on information from case files, informant reports, self‐made questionnaires, the Individual Schedule, CBI, behaviour problems inventory (BPI)(‐S, ‐01), DASH‐II, MOAS(+), DAS, autism spectrum disorder ‐behaviour problems for adults (ASD‐BPA) and the staff observation and aggression scale‐revised (SOAS‐R).…”
Section: Resultsmentioning
confidence: 99%
“…Ayrıca ZY'li grupta davranış sorunları ile psikiyatrik semptomların ilişkisi hala tartışmalı bir konudur. Bazı araştırmacılar davranış sorunlarını bir tip psikiyatrik bozukluk olarak kategorize ederken, diğerleri psikiyatrik tanıların dışında tutmuşlardır (22). Aslında davranış sorunlarının farklı yaklaşımlarla değerlendirilmesi, ZY'li yetişkinlerde psikiyatrik bozukluk yaygınlığının %13,9' dan % 75,2'ye kadar varan geniş bir aralıkta bulunmasına yol açan önemli sebeplerden biridir (23).…”
Section: Tartişma Ve Sonuçunclassified